Sodality dalam Perspektif Filsafat Pancasila: Jalan Setapak Menuju Sosiologi Indonesia - P. Setia Lenggono (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2021)
This article departed from the discomposure of Sediono M.P. Tjondronegoro regarding the weak integration of social sciences when applied to Indonesian society to actualize the ideals of independence. For this regard, a methodologically and theoretically clear philosophy of Indonesian Sociology—based on aspects of ontology, epistemology and axiology which are relevant to the nation's ideology—is important to be placed as the basis for the world view of social sciences developed in Indonesia. In this context, this article intends to elaborate the concept of Sodality being developed by Tjondronegoro as the core of Pancasila to be an alternative guidance in the scientific development of Indonesian Sociology. This research is a literature study which focuses on Tjondrnegoro’s works and other publication on social and historical reality of Indonesian society to be analysed through philosophical perspectives. Based on the social and historical reality of Indonesian society, the development of Indonesian Sociology as a national ideology-oriented social science should not be merely based on reasoning but also on intuition or the whisper of the heart and on experience. While rational consideration is not ignored, it is not considered as the only way to the sought truth. Even though Indonesian Sociology departs from a speculative thinking, by the course of time it is expected that it will be manifested as a scientific paradigm through a persuasive process that people might accept.